Fabrication of microscale carbon nanotube fibers - Sun, Gengzhi (2013)
Carbon nanotubes (CNTs) have excellent mechanical, chemical, and electronic properties, but realizing these excellences in practical applications needs to assemble individual CNTs into larger-scale products. Recently, CNT fibers demonstrate the potential of retaining CNT's superior properties at macroscale level. High-performance CNT fibers have been widely obtained by several fabrication approaches. Here in this paper, we review several key spinning techniques including surfactant-based coagulation spinning, liquid-crystal-based solution spinning, spinning from vertical-aligned CNT arrays, and spinning from CNT aerogel. The method, principle, limitations, and recent progress of each technique have been addressed, and the fiber properties and their dependences on spinning parameters are also discussed.